1992
DOI: 10.1136/gut.33.5.668
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil antibodies in inflammatory bowel disease: prevalence and diagnostic role.

Abstract: Anti-neutrophil antibodies have been shown in sera from patients with a variety of inflammatory diseases. Those reacting with compo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(80 citation statements)
references
References 23 publications
9
68
3
Order By: Relevance
“…These results are consistent with those in previous reports [2,3,[6][7][8][9], whereas Hibi and colleagues [17] reported that the frequency of ANCA by fixed-neutrophil ELISA was only 35% in Japanese patients with UC. This discrepancy seemed to be ascribed to the difference in neutrophil fixation, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those in previous reports [2,3,[6][7][8][9], whereas Hibi and colleagues [17] reported that the frequency of ANCA by fixed-neutrophil ELISA was only 35% in Japanese patients with UC. This discrepancy seemed to be ascribed to the difference in neutrophil fixation, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…10,11 TM has been identified as a putative auto-antigen of UC. Das et al 10 detected antibody reacting against porcine TM in UC sera.…”
Section: Discussionmentioning
confidence: 99%
“…ANCA can be detected in sera from patients with a wide variety of inflammatory diseases including UC. In one study of 50 patients with UC, 54% were shown to be either p-ANCA or c-ANCA positive but none of these antibodies reacted with PR3 or MPO [18]. In another study, ANCA-positive patients with UC were followed for a year during which no evidence of glomerulonephritis was found [19].…”
Section: Case Reports Of Uc Related Nephritismentioning
confidence: 99%